2014
DOI: 10.2459/jcm.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc in the prediction of early atrial fibrillation relapses after electrical or pharmacological cardioversion

Abstract: Our preliminary results suggest that CHA2DS2-VASc score could be useful in evaluating the risk of early recurrence of atrial fibrillation after cardioversion. This information may have implications for disease monitoring and treatment strategies in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…A total of 2408 records were analyzed. After the first evaluation of titles and abstracts, 22 studies were screened and of these 15 were excluded with reasons as reported in Figure S1, while the remaining seven were analyzed as full‐paper . Thereafter the seven corresponding authors were contacted for joining the patient‐level meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2408 records were analyzed. After the first evaluation of titles and abstracts, 22 studies were screened and of these 15 were excluded with reasons as reported in Figure S1, while the remaining seven were analyzed as full‐paper . Thereafter the seven corresponding authors were contacted for joining the patient‐level meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter the seven corresponding authors were contacted for joining the patient‐level meta‐analysis. Three authors agreed to share data and were included in qualitative and quantitative analysis (Figure S1 and Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients undergoing electrical or pharmacological cardioversion, the CHA 2 DS 2 -VASc score emerged as a significant predictor of early recurrence of AF [10]. Similarly, in the “Leipzig Heart Center AF Ablation Registry,” the CHA 2 DS 2 -VASc score was associated with both early and late relapses of the arrhythmia [11].…”
Section: Discussionmentioning
confidence: 99%
“…Falsetti et al suggested that the CHA 2 DS 2 VASc score could be useful in evaluating the risk of early recurrence of AF after electrical and pharmacological CV …”
Section: Discussionmentioning
confidence: 99%